Vicious [videorecording (DVD)] : the finale - Jacobi, Derek; McKellen, Ian; De la Tour, Frances, 1944-; Rheon, Iwan, 1985- (PBS Distribution, 2016)
It returns for an hour-long special series finale (episode 14), charting a year in the life of our beloved characters. Freddie and Stuart are back, joined as ever by Violet, Ash, Penelope and Mason. In spring, Freddie and Stuart attempt to hide their recently gained inheritance. Violet has financial troubles after her recent divorce and Ash struggles to meet his rent. Signs of Freddie and Stuart's expenditure, soon threatens the pretense as their home is overrun with guests.